1997
DOI: 10.1002/(sici)1097-0142(19970615)79:12<2354::aid-cncr9>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Postsurgical adjuvant therapy for melanoma

Abstract: IFN-alpha appears to be effective as adjuvant therapy for high risk melanoma patients and the risk/benefit ratio appears to be very favorable. The authors' next goal is to separate those patients who might benefit from adjuvant therapy from those who are cured after the surgical intervention only.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The Dermatologic Cooperative Oncology Group (DeCOG) trial demonstrated durable improvement in both RFS and OS [ 29 ], while the French Cooperative Group trial demonstrated significant extension of RFS and a clear trend towards increased overall survival ( p = 0.059) [ 30 ]. The Italian Skin Cancer Foundation, Austrian Malignant Melanoma Cooperative Group, and Scottish Melanoma Group clinical trials demonstrated significant improvement in RFS, but no improvement in OS [ 31 33 ]. However, no improvement in either RFS or OS was seen in the WHO Melanoma Programme, AIM HIGH Study-United Kingdom Coordinating Committee on Cancer Research, EORTC 18871, or ECOG 1690 trials [ 22 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Dermatologic Cooperative Oncology Group (DeCOG) trial demonstrated durable improvement in both RFS and OS [ 29 ], while the French Cooperative Group trial demonstrated significant extension of RFS and a clear trend towards increased overall survival ( p = 0.059) [ 30 ]. The Italian Skin Cancer Foundation, Austrian Malignant Melanoma Cooperative Group, and Scottish Melanoma Group clinical trials demonstrated significant improvement in RFS, but no improvement in OS [ 31 33 ]. However, no improvement in either RFS or OS was seen in the WHO Melanoma Programme, AIM HIGH Study-United Kingdom Coordinating Committee on Cancer Research, EORTC 18871, or ECOG 1690 trials [ 22 , 34 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to this broad spectrum of biological activities, a variety of potential therapeutic uses have been established for interferons. In particular, genetically engineered interferon-␣2 (rh IFN-␣2) produced by recombinant DNA technology, is currently being used worldwide in management of various neoplastic disorders and chronic viral diseases including hairy-cell leukemia, multiple myeloma, chronic myelogenous leukemia (CML) [5][6][7], renal cell carcinoma [8], malignant melanoma [9], and hepatitis [10]. Interferon-␣2b (IFN-␣2b), available in market as both lyophilized and soluble injectable preparations, is the most widely used subclass in clinical settings.…”
Section: Introductionmentioning
confidence: 99%